Examining the Role of Economic Actors in Post-war Reintegration Processes: Case of Sierra Leone. - Iwara, MaryAnne (Advances in Social Sciences Research Journal, 2021)
This paper examines post-conflict peacebuilding activities in Sierra Leone by critically looking at the role of economic actors in the reintegration process of its post-war Disarmament Demobilization, and Reintegration (DDR) initiative. The civil war that lasted for 11 years in Sierra Leone, put doubts on the national governments ability to effectively provide both victims and perpetuators, the necessary protection and assistance needed to fully assume responsibilities within the communities. Because of this, poverty was further entrenched, thereby increasing the countries susceptibility to return to conflict. Though reintegration processes are continuous, integrative and involve exhaustive budgetary commitments, the process, in Sierra Leone was short-termed, not well coordinated and took time to begin delivering. With the United Nations, World Bank and the weak national government leading the process, financing was often insufficient or late, in combination with the lack of a coherent planning strategy; all these factors contributed to lapses in socio-economic profiling, skills and vocational training and spread disillusionment and resentment among ex-combatants and victims. Using content analysis, the paper argues that, post-war countries need active, equitable and profitable economic sectors if they are to graduate from conflict and from post-conflict aid-dependency. Moreover, as social contracts and corporate social responsibility to communities they govern and operate in, economic actors must create enabling environments and, generate jobs to support legitimate local capacities. The utility of this paper lies in the idea that for any post-conflict country to attain long-term social and economic development, reintegration programme design and activities, must holistically incorporate critical economic actors.